PHYTOCHEMICAL STUDY OF THE RHIZOME OF CURCUMA HEYNEANA VAL. ET V. ZIJP ISOLATION AND IDENTIFICATION OF TERPENOID COMPONENTS - Firman, Kurnia
Among the zingiberaceous plants of the genus Curcuma found in Indonesia, there are only C. xanthorrhiza Roxb., C. domestica Valet., and C. zedoaria (Bergius) Roscoe, whose chemical constituents and their biological activities have been investigated and reported in the literature. The chemical contituents which have been isolated and identified mainly consist of hydrocarbon and oxygenated mono and quiterpenoids but none of these three species are reported containing diterpene. Of Curcuma zedoaria which has been intensively studied particularly in Japan, there has been proposed some possible biogenetic pathways of the formation of the sesquiterpenoids, and moreover, a biomimetic transformation of one sesquiterpene to other sesquiterpenes found in this plant has been carried out. In addition to the three Curcuma species mentioned above, C. heyneana Val. et V. Zijp, is widely used in traditional medicine and traditional cosmetics. It has been found that the juice pressed from the fresh rhizome showed an anthelmintic activity against pig Ascaris in vitro, and the main part of the activity was found to occur in its essential oil fraction. However, there is no available chemical information on this plant to date. The discovery and identification of chemicalcompounds the constituents of medicinal plant is one of the rational basis required for its use in modern medicine, in the form of its preparation or its extract, moreover, in the pure form of chemical compound. The objectives of the study is to isolate and to identify the chemical constituents of the rhizome and particularly the essential oil part of the fresh rhizome of C. heyneana, specially the terpenoids. It is hoped that the compounds isolated can be further subjected to the variety of biological tests for certain activities attributed to C. heyneana and other activities as well, to obtain a new therapeutic agent, and are also expected that the obtained compounds would be worthwhile for emotaxonomical and biogenetic studies of Curcuna spp.. The essential oil prepared by steam distillation of the rasped fresh rhizome and the methylene chloride and benzene extracts of the air dried sliced-rhizome were initially fractionated by column chromatography on silica gel eluted with gradient solvent of benzenechloroformacetone or n-hexane-acetone. The fractionations obtained were then repeatedly separated by column-, preparative thin-layer and preparative pressurized liquid chromatography. From the least polar fractions of the oil, by the combined GC-MS method there have been separated and detected 14 hydrocarbon monoterpenes and 29 hudrocarbon sesquiterpenes. By comparison of the mass-spectral andchromatographic data with those found in the references, ten of fourteen monoterpenes were identified as clofenchene, camphene, A-pinene, sabinene, myercene, a-terpinene, limonene, L-terpinene, p-cymene and terpinolene (XII-XXI) and nine of twenty nine sesquiterpenes were identified as a-copaene, 8-elemene, a-cubebene, A-elemene, 1- aryophylllene, A selinene, Scadinene, a-muurolene and (-) calamenene (XXII-XXX). These compounds are found not only in Curcuma spp., but also in other zingiberaceous as well as other plants and they are thus not characteristic to the Curcuma species. From other fractions of the essential oil, eight compounds (I-VII) have been obtained. By the spectroscopic method and finally by direct comparison with authentic samples, compounds I, III, V and VI were respectively identified as germacrone, dehydrocurdione, isocurcumenol and curcumenol. Compounds IIA and IIB were obtained as an epimeric mixture which was then separated by recycling high pressure liquid chromatography, by comparison of their spectroscopical data with those reported in the literature they were found to be the spirolactones, curcumanolide A and curcumanolide B. Based on its 1H and 13C NMR data and supported by conventional and long range 1H-13C shift correlated 2D NMR (COSY) spectra, compound IV was identified as a compound whose structure coincides with that of zerumbone. All of these seven sesquiterpenes are known compounds, which have been isolated mainly from C. zedoaria except for zerumbone. The eighth compound (VII) is a new compound , to date there are no publications reported the isolation of this compound either from Curcuma spp. or from other zingiberaceous and other plants. This compound is a guaiane-type sequiterpene named oxycurcumenol. and ased on its spectroscopical data, this compound has been elucidated as 7,11-epoxide of curcumenol. From the NOE observation in the difference spectrum which was then confirmed by X-ray analysis, the configuration of this epoxide was assigned as 0-epoxide. The absolute stereochemistry of this compound was determined by chemical method, namely by the direct transformation of curcumenol whose absolute structure has been known and established by the X-ray crystallography. This transformation has been carried out by oxidation of curcumenol using m-chloroperbenzoic acid to give the 0-epoxide which is identical to the isolated new compound (VII) in every respect including the optical property. From the methylene chloride extract there have been isolated a colorless oily compound (VIII) in addition to germacrone, dehydrocurdione and curcumenol. Compound VIII has also been isolated from the benzene extract in addition to curcumanolide A and curcumanolide B, dehydrocurdione and curcumenol. By comparing the spectroscopic and other physicochemical data with those reported in the references, this compound was elucidatedas a diterpene of the labdane type, (E)-labda- (17),12-diene-15,16-dial. On the thin-layer chromatogram of both extracts, the presence of oxycurcumenol spot can be clearly observed. From the literature study and from the results mentioned above,it can be concluded that the isolated hydrocarbon mono- and sesquiterpenes are not characteristic for Curcuma heyneana and other Curcuma spp. as well as ther zingiberaceous plants. Oxycurcumenol is found to be characteristic for Curcuma heyneana, and except of zerumbone, the six oxygenated sesquiterpenes were also found in Curcuma zedoaria. This may indicate the close chemotaxonomical relationship between these two species, since the occurence of these compounds particularly germacrone and dehydrocurdione which were considered as the precursor of a variety of sesquiterpeneoids is mainly found in these two species among the genus Curcuma. The isolation of zerumbone, which was the main component of Zingiber zerumbet and Z. amaricans, from the genus Curcuma has not been reported previously. The isolation of the diterpene of the labdane type from Curcuma spp., where the labdane is the only type of diterpene known to occur in the zingiberaceous plants, has also been for the first time. The reported possible biosynthesis of curcumenol and isocurcumenol from germacrone through dehydrocurdione as a possible intermediate in C. zedoaria, and the reported conversion of dehydrocurdioneby cyclization to curcumenol, isocurcumenol and curcumanolide A and B are presumably also taking place in C. heyneana, since all of the compounds involved has been found in C. heyneana. The isolation of curcumanolide A and B from the benzene extract indicate that the conversion of dehydrocurdione into spirolactones takes place even under milder condition. Isocurcumenol which was found only in the oil but not in the extract is strongly supposed being the artefact derived from pyrolytic conversion during steam distillation of the oil. The results of this study has made a contribution to the current chemical information of Indonesian medicinal plants, and thus makes the phytochemical study of Indonesian medicinal plants goes one more step forward. An occasion for investigation of biological or pharmacological activities using the isolated compounds is thus more widely open.